2002
DOI: 10.1103/physrevlett.89.037001
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced In-Plane Anisotropy of Phonon Anomalies inYBa2Cu3O6.6

Abstract: The dispersion of the Cu-O bond-stretching and bond-bending vibrations in YBa(2)Cu(3)O(6.6) has been studied by high resolution inelastic neutron scattering. While the behavior of the bond-bending vibrations can be well accounted for by a simple potential model, the bond-stretching vibrations show a highly anomalous behavior. The displacement pattern of the most anomalous phonons is in principle consistent with dynamic charge stripe formation. However, charge stripes would have to extend along the a axis and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 17 publications
2
46
2
Order By: Relevance
“…Finally, inelastic neutron scattering experiments pointed to an anomalous behavior in the dispersion of the in-plane longitudinal optical phonons with wave vectors [0, 0.25, 0] in the YBCO superconductors. This corresponds to bond stretching vibrations being associated with dynamical charge fluctuations on the Cu ions driven by the displacement of the neighboring ligand environment of the O atoms 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, inelastic neutron scattering experiments pointed to an anomalous behavior in the dispersion of the in-plane longitudinal optical phonons with wave vectors [0, 0.25, 0] in the YBCO superconductors. This corresponds to bond stretching vibrations being associated with dynamical charge fluctuations on the Cu ions driven by the displacement of the neighboring ligand environment of the O atoms 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that this anisotropy matches the one previously observed in the anomalous dispersion of copper-oxide phonon modes in YBCO 6+δ . [42][43][44] Measurements of YBCO 6.55 and YBCO 6.6 crystals under the same experimental conditions further allowed us to compare the overall intensities of the incommensurate peaks in both crystals. The peak along K is about ∼ 25% less intense in YBCO 6.55 than it is in YBCO 6.6 ; the intensity difference along H is correspondingly larger.…”
mentioning
confidence: 99%
“…Whereas the corresponding breathing mode at (π, π) shows much smaller softening and no anomalous broadening (Fig.5). This effect appears to be generic for cuprates and detailed neutron scattering studies have been reported for La 2−x Sr x CuO 4 [18,19,20,21], YBa 2 Cu 3 O 6+x [19,22,23] and also for Bi-based cuprates [24]. This certainly shows that there are phonons which couple rather strongly to the charge carriers that contribute to superconductivity, and one may ask what is special about the interaction of strongly correlated electrons and phonons.…”
Section: Renormalization Of Breathing Phononsmentioning
confidence: 76%